Mechanism of action and experimental validation of key genes common to diabetic retinopathy and coronary heart disease based on multiple bioinformatics investigations - Jiang, Fanli; Yin, Shi; Zhang, Xinjin (Frontiers in Genetics, 2025)
IntroductionThe relationship between diabetic retinopathy (DR) and coronary artery disease (CHD) has been established as a reliable predictor. However, the underlying mechanisms linking these two conditions remain poorly understood. Identifying common key genes could provide new therapeutic targets for both diseases.MethodsPublic databases were used to compile training and validation datasets for DR and CHD. Machine learning algorithms and expression validation were employed to identify these key genes. To investigate immune cell differences, single-sample gene set enrichment analysis (ssGSEA) and the Wilcoxon test were applied. Spearman correlation analysis further explored the relationship between key genes and immune cell variations. Additionally, potential therapeutic drugs targeting these key genes were identified and a key gene–drug network was constructed. The role of the key genes in the pathogenesis of DR and CHD was further examined through reverse transcription-quantitative polymerase chain reaction (RT-qPCR).ResultsConsistent expression trends observed across datasets (GSE221521, GSE113079, GSE189005, GSE42148) led to the identification of HIRIP3 and ZNF416 as key genes. In GSE221521, HIRIP3 was positively correlated with CD56 bright natural killer cells (cor = 0.329, P < 0.001) and type 1T helper cells (cor = 0.327, P < 0.001), while ZNF416 showed significant correlations with CD4 T cell activation (cor = 0.340, P < 0.001) and type 1T helper cells (cor = 0.273, P < 0.05). Moreover, 82 transcription factors (TFs) were predicted, including SP3. Binding free energy calculations for key genes and potential drugs suggested stable binding conformations. RT-qPCR results revealed elevated expression of both HIRIP3 and ZNF416 in the control group compared to the DR with CHD (DRwCHD) group, with only ZNF416 showing significant differences between the groups (p < 0.05).DiscussionThese findings highlight HIRIP3 and ZNF416 as crucial genes in DR and CHD detection, providing a foundation for identifying novel therapeutic targets for both diseases.